Pembimbingan Kepribadian Klien Pemasyarakatan Mataram (Bentuk Pribadi yang Berjiwa Besar dan Peduli Terhadap Sesama) - Mujiburrahman Mujiburrahman; Lu'luin Najwa; Moh. Zainul Ahzan; M. Najamuddin (Fakultas Ilmu Pendidikan dan Psikologi, 2024)
Community service was carried out at the Mataram Class II Correctional Center. The target of this activity is 40 correctional clients. In the implementation of this community service, training and mentoring methods are used which are followed by employees and inmates in correctional institutions. The training consists of two stages, where the first stage involves an explanation of cognitive guidance, while the next stage involves individual assistance to practice materials related to cognitive guidance. This training and mentoring runs in accordance with the goals and plans that have been set. This program received a positive response from Bapas and Mataram Class II correctional clients. This activity provides additional knowledge about positive behavior patterns, the development of potential to live independently, and motivation to live normally in society. In the process of guidance activities, correctional clients actively discuss and convey problems faced in community life